Employment effects of educational measures for work-injured people - Henning Bach; Nabanita Datta Gupta; Jan Høgelund (Institute for the Study of Labor (IZA), 2007)
Vocational rehabilitation in the form of education is the cornerstone of governmental rehabilitation programs for the work-disabled in many countries. Merging a 2004 Danish survey to register information from the Danish National Board of Industrial Injuries, we assess the employment effects of educational measures for the work-injured, by simultaneously estimating the hazard rate to education and the return to work, controlling for unobserved heterogeneity and the endogeneity of education. In addition, we allow for any enhanced employment effects of a unique wage subsidy program in Denmark, giving employers a partial wage subsidy for disabled workers' wages, by distinguishing between education effects of a return to wage-subsidized work versus a return to ordinary work. Unlike previous studies, we find a positive impact of educational measures on the probability of returning to work for the work injured and a stronger effect for a return to wage-subsidized employment compared to a return to ordinary employment
urn:nbn:de:101:1-20080415189
Keywords: 330; Berufliche Rehabilitation; Arbeitsunfall; Bildungsertrag; Beschäftigungseffekt; Dänemark